Two-micrometer circle site-specific recombination: the minimal substrate and the possible role of flanking sequences. - Jayaram, M (1985)
The 2-mum circle DNA of yeast encodes a site-specific recombination system (FLP recombination). The recombination region had been mapped earlier to a 65-base-pair (bp) segment within the 599-bp-long inverted repeats of the molecule. I have shown that the "minimal" FLP substrate resides in a 13-bp dyad symmetry plus an 8-bp core located within the 65-bp recombination region. Further, as determined by different in vivo assays, sequences extraneous to the minimal FLP site and the 65-bp recombination region can affect the efficiency of the recombination reaction.